L’étude de cas face à l’exemple : pratiques et enjeux dans l’enseignement de la géographie et de l’aménagement à l’université - Caroline Leininger-Frézal; Nicolas Douay; Marianne Cohen (Recherches en Éducation)
Geography and Urban planning teaching is focused on space in a general and theoretical point of view but it also deals with specific places. Using examples or case studies to teach geography or urban planning seems to be natural. This fact is largely based on a disciplinary legacy for which empirical geography is built around regional case studies. While geography has experienced different epistemological developments, it seems interesting to question the reality of teaching practices in contemporary geography education in the university. That is what this article proposes to do through the analysis of a corpus of interviews with French teacher-researchers in the geography or urban planning field.